Understanding How Green Intellectual Capital Influences Earnings Management: Insights from a Qualitative Study - Dwianika, Agustine; Mayangsari, Sekar (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
This qualitative study explores the influence of Green Intellectual Capital (GIC) on earnings management practices in Indonesian manufacturing firms. With increasing environmental concerns and corporate sustainability commitments, this research investigates how components of GIC, including green human capital, green structural capital, and green relational capital, contribute to ethical financial reporting. Semi-structured interviews were conducted with senior managers, financial officers, and sustainability officers in five listed manufacturing companies, involving a total of 15 participants. Each interview lasted between 60–90 minutes and was audio-recorded, transcribed, and analyzed using thematic coding to identify recurring patterns and divergent perspectives. The results reveal that strong GIC can act as an internal control mechanism, reducing the tendency toward earnings management by fostering environmental accountability and long-term strategic thinking. However, the study is limited by its relatively small sample size and reliance on self-reported data, which may not fully capture broader industry practices. These findings highlight the significance of embedding green values into intellectual resources to promote financial transparency while offering a foundation for future research with larger and more diverse samples.